2017
DOI: 10.1021/acssuschemeng.7b01354
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Energy Harvesting Devices: Attempts To Produce High-Performance Electrodes

Abstract: Dielectric elastomer transducers (DETs), essentially consisting of highly deformable insulating films sandwiched between electrodes, are able to convert mechanical work in electrical energy and vice versa. Although still immature, these represent a simple and low-cost alternative to already known technologies for harvesting energy from renewable sources, in this case converting environmental mechanical energies (e.g., wave energy, human body movement) to an electrical one. However, the development of this new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 54 publications
(72 reference statements)
0
15
0
Order By: Relevance
“…Tugui et al developed a highly stretchable freestanding electrode, PDMS–carbon black. By integrating such electrodes with a commercial silicone elastomer (Elastosil), an energy density of 1.1 mJ cm −3 was achieved under 200% strain …”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%
“…Tugui et al developed a highly stretchable freestanding electrode, PDMS–carbon black. By integrating such electrodes with a commercial silicone elastomer (Elastosil), an energy density of 1.1 mJ cm −3 was achieved under 200% strain …”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%
“…By properly designing polysiloxanes in terms of structure, molecular weight and crosslinking pattern, it was found that a silicone elastomer based on PDMS ( M w = 80,000 Da) containing 8.4 mol.% vinyl groups crosslinked by thiol-ene addition with a PDMS ( M w = 35,000 Da) containing 16.5 mol.% SH group along the chain, without other additions, incorporated in a DEA developed a lateral actuation of 15% when applying an electric field E = 20 MV/m ( Figure 5 a) [ 53 ]. A DEG built from three circular layers of common silicone with a diameter of 120 mm and coaxial circular stretchable electrodes of 60 mm diameter also based on silicone but embedding 25 wt.% carbon black was able, at 200% strain, to harvest almost 1 mJ ( Figure 5 b) [ 79 ]. An energy harvesting efficiency of η = 8.84% was achieved with a DEG based on silicone filled with 2 wt.% TiO 2 nanotubes and carbon black electrodes ( Figure 5 c) [ 80 ].…”
Section: Classic Amorphous Silicones Renewed For Emerging Applicationsmentioning
confidence: 99%
“…Composites based on silicones and conductive fillers are also being studied as compliant electrodes. Considering that the carbon black particles represent the cheapest powder that can be used as a conductive filler, a rubber electrode was fabricated by incorporating 25 wt.% of carbon black into a high molecular weight PDMS [ 79 , 81 ]. The electrical conductivity was about 0.1 S·cm −1 at 150% strain, remaining almost unchanged even after a few hundred stretching cycles ( Figure 5 d).…”
Section: Classic Amorphous Silicones Renewed For Emerging Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cazacu et al . reported a 20 wt% CB/PDMS composite with a moderate conductivity of 0.1 S/cm 26 . Opris et a l. reported the preparation of PDMS/graphite nanocomposites with a conductivity of 0.35 S/cm with graphene nanoplates (GNPs) content of 20 wt.%, while the conductivity below this filler content was unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%